(untitled) (Architecture Image Studies, 2025)
This study examines the improvement of students’ science literacy through science learning oriented towards Education for Sustainable Development (ESD), using mangrove forests as a learning resource. The method used is an experiment with a “Pretest-Posttest Control Group Design”, which allows for a comparison of students’ science literacy abilities before and after treatment. The experimental class followed ESD-based learning using mangrove forests, while the control class continued to use conventional methods. A significant difference in science literacy improvement was found between the experimental and control groups (Mann-Whitney test, Asymp.sig. = 0.00), with the experimental class showing a larger increase. Their average post-learning score was 75.29, which was higher than the control group’s average of 66.4. A challenge of this learning approach is the potential danger to students from flooded forest conditions. Therefore, student health and safety must be taken into consideration, for example, by using Personal Protective Equipment (PPE) during visits. With this measure, ESD-based science learning in the field remains safe while effectively improving students’ science literacy.